Downward Real Wage Rigidity and Equal Treatment Wage Contracts: Theory and Evidence - Andy Snell; Heiko Stüber; Jonathan P. Thomas (Institute of Labor Economics (IZA), 2018)
Recent dynamic contracting models of downward real wage rigidity with "equal treatment" – newly hired workers cannot price themselves into jobs by undercutting incumbents – imply that real wages are relatively rigid in "bad" times but upwardly flexible during "good" times. We use an administrative panel dataset to establish that such asymmetries are a feature of West German labor markets. We find that the elasticity of real wages with respect to output is very close to zero in downswings but large and highly significant in upswings. In a separate analysis we find that after controlling for match fixed effects the cyclicality of new hire wages is approximately the same as that for incumbent wages regardless of whether or not they joined the establishment from unemployment This is supportive of equal treatment. We also show that a four parameter version of the equal treatment contracting model of Snell and Thomas (2010) can replicate reasonably well the salient time series properties and co-properties of real wages, output, and unemployment, in particular the asymmetric response of wages to output that we find in the data.
Keywords: E24; E32; C23; 330; business cycles; employment; unemployment; real wage rigidity; GDP growth; models with panel data